Identity clinic: a study on the psychosocial suffering collective - Jörg, Simone (Revista de Psicologia, 2015)
This paper was developed on the experience of master’s research for two and a half years, with the object of his study to understand the construction of identity with emancipatory sense of residents of the 1st village-train in the State of São Paulo, the town of “Paranapiacaba”, in Santo André, listed by historical, cultural and environmental inserted in a context of intense psychosocial distress, which figure in a significant incidence of panic disorders, depression and frequent cases of suicide. From the theoretical basis proposed by Antonio da Costa Ciampa, it was analyzed the narrative of the life stories of 11 villagers, old and new, with different professional training, in different age groups, which, corroborating with observations “in loco”, can conclude that the suffering is based on the imposition of an identity politics of recognition perverse, and legitimized by instrumental rational logic-finalist in the public discourse coupled with the crisis of meaning.